ANÁLISIS SOCIO-JURÍDICO DESDE EL DERECHO INTERNACIONAL PÚBLICO DEL CONFLICTO ENTRE ARGENTINA E INGLATERRA, POR LA SOBERANÍA DE LAS ISLAS MALVINAS (I PARTE) SOCIO (2016)
This article is a partner legal analysis on the territorial sovereignty dispute between Argentina nation and the United Kingdom over the islands known as the Malvinas by Argentina. The methodology used is the analytical empirical, where the review of various texts illustrates indirectly the intention of the text, which is to present sociocultural impact of war, as apparently abandoned institution of international law, and mainly civilized nations, as a formula for resolving conflicts between sovereign. We present the first installment of this research.